2020
DOI: 10.3390/ijerph17176054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inclusive Talent Development Model on Turnover Intention of New Generation Employees: The Mediation of Work Passion

Abstract: The high turnover rate of new generation employees is becoming an increasingly important issue for business and academia. Based on self-determination theory and conservation of resource theory, our study explores the impact of the inclusive talent development model on the turnover intention of new generation employees and the mediating role of work passion. Based on the questionnaire of 290 new generation employees’ data from China, after common method biases and reliability and validity tests, we used SPSS, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 48 publications
0
28
0
1
Order By: Relevance
“…The empirical research on the influence of distributed leadership on employees’ behavior is very insufficient. It is worth noting that Fang et al (2020) discussed the influence of leadership style on the behavior of the new generation of employees, he focused on the negative behavior (resignation behavior) of new generation employees, not positive behavior (proactive behavior). Our research has found the antecedents of the new generation of employees’ proactive behavior (distributed leadership) from the leadership style, and provided a new perspective for inspiring the new generation of employees’ proactive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical research on the influence of distributed leadership on employees’ behavior is very insufficient. It is worth noting that Fang et al (2020) discussed the influence of leadership style on the behavior of the new generation of employees, he focused on the negative behavior (resignation behavior) of new generation employees, not positive behavior (proactive behavior). Our research has found the antecedents of the new generation of employees’ proactive behavior (distributed leadership) from the leadership style, and provided a new perspective for inspiring the new generation of employees’ proactive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This situation leads them to be very interested in innovative elements, knowledge sharing, and a good atmosphere of cooperation ( Hernaus and Vokic, 2014 ). Therefore, new generation of employees has higher psychological expectations for interpersonal relationships, organisational compatibility and comfort, knowledge and skills, and a growth environment ( Fang et al, 2020 ). New generation of employees with a clear career plan and good psychological cognition attach great importance to fulfilling the psychological contract ( Shri, 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, 942 valid questionnaires were collected, for an overall effective response rate of 44.86%. We used Harman's single-factor test, which has been frequently used in previous research, such as Barbosa et al [40] and Fang et al [41], to verify whether there was common method bias. The test showed that there were several different factors, six of which had eigenvalues greater than 1.…”
Section: Participants and Proceduresmentioning
confidence: 99%